Constitutionalisation of Civil Law, Civilisation of Constitutional Law and Way towards Private Constitutional Law - Didžiulis, Laurynas (Vilnius University Open Series, 2024)
Due to the resourceful case law of the Lithuanian Constitutional Court and the doctrinal attitudes of its justices, during the most recent decades in the Lithuanian legal discourse, the opinion has been established that the constitutional law is the true foundation of the legal system, whereas the civil law is merely an ordinary branch of Law fully determined by the former. Even more – the acknowledgment that the Constitution is a main source of the civil law was followed by the denial of the civil law rules to be a source of the constitutional law and any reverse effects. This approach, which has become dogmatic in Lithuania, is understood as a consequential result of the constitutionalisation of the civil law. However, more detailed theoretical analysis, presented in this article, on the relationship between the constitutional law and the civil law as well as the case law of the Constitutional Court involving the application of the civil law rules in a constitutional adjudication denies such simplistic understanding. The relationship between the branches of law in question seems to be much more subtle and complex than judging superficially from the perspective of legal stratification into the constitutional law and the ordinary law. Ironically, the understanding proposed by constitutionalists where the constitutional law is a higher law to which the civil law is fully subordinated provokes a legal scholar to proceed further and discover signs of the formation of the private constitutional law. This, in turn, demands new reflection on the relationship between the constitutional law and the civil law. Hence, in the present article, by applying functional, systemic and comparative analysis, and by taking into account the case law of the Constitutional Court, the author seeks to find out the relationship between the constitutional law and the civil law which is fundamental for every legal system.
Keywords: civil law; constitutional law; private constitutional law; legal system; normative hierarchy